Ectopic Expression of the Wild Grape WRKY Transcription Factor VqWRKY52 in Arabidopsis thaliana Enhances Resistance to the Biotrophic Pathogen Powdery Mildew But Not to the Necrotrophic Pathogen Botrytis cinerea - Wang, Xianhang; Guo, Rongrong; Tu, Mingxing; Wang, Dejun; Guo, Chunlei; Wan, Ran; Li, Zhi; Wang, Xiping (Frontiers in Plant Science, 2017)
WRKY transcription factors are known to play important roles in plant responses to biotic stresses. We previously showed that the expression of the WRKY gene, VqWRKY52, from Chinese wild Vitis quinquangularis was strongly induced 24 h post inoculation with powdery mildew. In this study, we analyzed the expression levels of VqWRKY52 following treatment with the defense related hormones salicylic acid (SA) and methyl jasmonate (MeJA), revealing that VqWRKY52 was strongly induced by SA but not JA. We characterized the VqWRKY52 gene, which encodes a WRKY III gene family member, and found that ectopic expression in Arabidopsis thaliana enhanced resistance to powdery mildew and Pseudomonas syringae pv. tomato DC3000, but increased susceptibility to Botrytis cinerea, compared with wild type plants. The transgenic A. thaliana lines displayed strong cell death induced by the biotrophic powdery mildew pathogen, the hemibiotrophic Pseudomonas syringe pathogen and the necrotrophic pathogen B. cinerea. In addition, the relative expression levels of various defense-related genes were compared between the transgenic A. thaliana lines and wild type plants following the infection by different pathogens. Collectively, the results indicated that VqWRKY52 plays essential roles in the SA dependent signal transduction pathway and that it can enhance the hypersensitive response (HR) cell death triggered by microbial pathogens.